Rancang Bangun Sistem Informasi Bimbingan Konseling Berbasis Web Pada SMA N 01 Sindang Danau - Bakti Eka Putra; Ade Surahman; Auliya Rahman Isnain (PT. Tech Cart Press, 2023)
Technology develops, the world of education is of course very supportive for the progress of the world of education, in this case in the field of guidance and counseling. This led to the creation of an information counseling guidance system design at sman 01 sindang lakes. Guidance counseling is a process in which a professional provides assistance to a person or individual to overcome the problems they face. Therefore, the school is not only a place for teaching and learning, but also directly or indirectly monitors the progress of its students. However, there are still a number of obstacles that must be implemented, one of which is experienced by SM N 01 Sindang Danau which manages student guidance and counseling services. Another problem is that all records are still manual in nature, such as recording cases of students who violate, starting from filing, dates, names, types of cases to letters sent to the parents of students who are often not conveyed properly. The website-based guidance and counseling information system at sman 01 trial lake has gone through the Black Box test and got a result of 93.93% with a very decent predicate. The system facilitates counseling guidance services starting from the information obtained by the student's guardian and facilitates the performance of the guidance and counseling teacher for reporting to related parties such as the teacher's guardian and the students themselves, and will also provide counseling to students and provide direction to student guardians so that the school and student guardians play a direct role in character education, especially in the field of guidance and counseling.